Determination of Glutamate and GABA Released by Mouse Embryonic Stem Cells Using HILIC-ESI-MS/MS - Lv, Haoyu; Tang, Yabin; Sun, Fan; An, Shimin; Yang, Xinjie; Li, Wenbin; Wang, Xiaosheng; Zhu, Liang (Natural Products Journal, The, 2020)
Background: In recent years, more and more researches have shown that neurotransmitters can also be synthesized and released by peripheral non-neural cells. However, specificity and high sensitivity detection means were required for confirming ESCs autocrine glutamate and γ - aminobutyric acid (GABA). Glutamate and GABA are water-soluble and polar compounds which cannot be retained on a reversed phase C18 column, and their contents are often at a trace level. On the other hand, the biological matrix such as cell culture fluid contains a large number of amino acids, vitamins, carbohydrates, inorganic ions and other substances. Therefore, the main problem is the selection of the chromatographic column to avoid matrix interference. Objective: To establish a rapid and reliable method for the simultaneous determination of glutamate and GABA released from embryonic stem cells based on analytical chemistry. Methods: Glutamate and GABA released from mouse embryonic stem cells were determined on the basis of hydrophilic interaction chromatography coupled with electrospray ionization tandem Mass Spectrometry (HILIC- ESI- MS/MS), using isotope internal standards and substitution matrix method. Results: Undifferentiated embryonic stem cells autocrine glutamate and GABA and will reach releasing- reuptacking dynamic equilibriums at different time points. In contrast, neither glutamate nor GABA releasing could be detected from the MEFs, indicating the specificity release of the mESCs in the applied analytic method. Conclusion: A novel, simple, sensitive, selective and quantitative method was developed for determination of the glutamate and GABA from mouse embryonic stem cells.
Keywords: neurotransmitter